Increasing Community Self-Reliance through Maggot at Villa 1 Asri Waste Bank, Bekasi Regency: Peningkatan Kemandirian Masyarakat melalui Maggot pada Bank Sampah Villa 1 Asri, Kabupaten Bekasi - Sumiyarti, Sumiyarti; Rahayu, Hartini Rahayu; Ratna, Ratna Ningsih (CONSEN: Indonesian Journal of Community Services and Engagement, 2024)
This community service activity (PkM) is intended to help increase income from organic waste management through maggot cultivation. The activity method used is training, by applying appropriate technology in the form of portable bioponds and drying machines to make dried maggot. The activity implementation period is November 26 to December 23, 2022. The results of the activity show the potential for increased income and environmental independence in managing organic waste through maggot. Before the PkM activity was carried out, the source of income from maggot only came from fresh maggot. After the PkM activity, there is an additional source of income from dried maggot products, with a range between Rp23 thousand - Rp30 thousand for every one kilogram of dried fresh maggot. The application of portable bioponds has increased the amount of fresh maggot production between 60 kilograms - 80 kilograms.  The application of portable bioponds as maggot enlargement media has increased the amount of organic waste that is managed independently. Before the PkM activity, the amount of organic waste managed was 240 kilograms - 320 kilograms. After the PkM activity, the amount of managed waste increased to 360 kg - 480 kg. In general, it can be concluded that PkM activities through the application of technology in maggot cultivation carried out by the Trisakti University PkM Team at the Villa 1 Asri Waste Bank have succeeded in increasing community independence both in terms of economy and environment.